Collision cascades overlapping with self-interstitial defect clusters in Fe and W. (2nd April 2019) - Byggmästar, J; Granberg, F; Sand, A E; Pirttikoski, A; Alexander, R; Marinica, M-C; Nordlund, K
Abstract: Overlap of collision cascades with previously formed defect clusters become increasingly likely at radiation doses typical for materials in nuclear reactors. Using molecular dynamics, we systematically investigate the effects of different pre-existing self-interstitial clusters on the damage produced by an overlapping cascade in bcc iron and tungsten. We find that the number of new Frenkel pairs created in direct overlap with an interstitial cluster is reduced to essentially zero, when the size of the defect cluster is comparable to that of the disordered cascade volume. We develop an analytical model for this reduced defect production as a function of the spatial overlap between a cascade and a defect cluster of a given size. Furthermore, we discuss cascade-induced changes in the morphology of self-interstitial clusters, including transformations between and dislocation loops in iron and tungsten, and between C15 clusters and dislocation loops in iron. Our results provide crucial new cascade-overlap effects to be taken into account in multi-scale modelling of radiation damage in bcc metals.